Analisis Keterbatasan Penguasaan Fi’il Amr dalam Maharah Kitabah dan Strategi Diferensiasi Pembelajaran - Ramdhani, Diyan Rifky; Athallah, Muhammad Hanif; Nandang, Ade (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Mastery of the fi'il amr in the Maharah Kitabah is an important productive grammatical competency, but it remains a major weakness of madrasah students, especially in boarding institutions with complex curriculum structures. This study aims to map the initial abilities of eighth-grade students in using fi'il amr in the Maharah Kitabah based on texts with the theme of natural beauty that are aligned with the Learning Outcomes of Phase D of the Independent Curriculum, and to identify the factors that influence it as a basis for formulating differentiated learning strategies. The study used a mixed descriptive method involving 40 students of Madrasah Mu'allimin Muhammadiyah Yogyakarta. Data were collected through written diagnostic assessments, observations of the learning process, and analysis of curriculum documents, then analyzed descriptively quantitatively and qualitatively. The results of the study indicate three ability profiles, namely students with comprehensive abilities (30%), grammatical abilities without contextualization (22.5%), and text comprehension without the ability to use fi'il amr productively (47.5%). These findings are influenced by the triple curriculum burden, the dominance of grammatical approaches, learning fatigue in the boarding school context, and mother tongue interference. This research emphasizes the importance of implementing differentiated learning based on diagnostic assessments to improve students' productive grammatical skills in the context of Islamic education with a complex curriculum